2000
DOI: 10.1074/jbc.m000894200
|View full text |Cite
|
Sign up to set email alerts
|

ATP Crossing the Cell Plasma Membrane Generates an Ionic Current in Xenopus Oocytes

Abstract: The presence of ATP within cells is well established. However, ATP also operates as an intercellular signal via specific purinoceptors. Furthermore, nonsecretory cells can release ATP under certain experimental conditions. To measure ATP release and membrane currents from a single cell simultaneously, we used Xenopus oocytes. We simultaneously recorded membrane currents and luminescence. Here, we show that ATP release can be triggered in Xenopus oocytes by hyperpolarizing pulses. ATP release (3.2 ؎ 0.3 pmol/oo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 49 publications
1
49
1
Order By: Relevance
“…It has recently been proposed that strong hyperpolarization of the oocyte (i.e. to Ϫ200 mV) may activate an ATP-selective conductance (16). However, our studies indicate similar hyperpolarizations activate a nonselective conductance that fails to saturate with prolonged hyperpolarization and recovers only slowly (i.e.…”
Section: Resultscontrasting
confidence: 78%
“…It has recently been proposed that strong hyperpolarization of the oocyte (i.e. to Ϫ200 mV) may activate an ATP-selective conductance (16). However, our studies indicate similar hyperpolarizations activate a nonselective conductance that fails to saturate with prolonged hyperpolarization and recovers only slowly (i.e.…”
Section: Resultscontrasting
confidence: 78%
“…It has been suggested that NTPDase1 could function as an ATP release channel. Release of ATP from NTPDase1-transfected Xenopus oocytes could be induced by hyperpolarizing pulses and required functional ecto-ATPase activity [143].…”
Section: Oligomeric Structurementioning
confidence: 99%
“…Since we could not inhibit the response by other known transport inhibitors, such as ABC transporter inhibitors, it seems likely that the ENT transporters are involved in both processes. Yet another possibility is that ATP is secreted by CD39 protein, recently recognized as an ATP-transporting protein (Bodas et al, 2000). As the ENT1 nucleoside transporters are distributed on nerve terminals and also on astrocytes and endothelial cells (Anderson et al, 1999), the cellular source of ATP-evoked purine efflux could be either nerve terminals, glial cells or endothelial cells.…”
Section: B Sperlágh Et Almentioning
confidence: 99%